2019
DOI: 10.3390/atmos10080451
|View full text |Cite
|
Sign up to set email alerts
|

High Contribution of Biomass Combustion to PM2.5 in the City Centre of Naples (Italy)

Abstract: A better knowledge of the local and regional sources of the atmospheric particulate matter provides policy makers with the proper awareness when acting to improve air quality, in order to protect public health. A source apportionment study of the carbonaceous aerosol in Naples (Italy) is presented here, in order to improve this understanding in a vulnerable urban area. The aim of this study is quantifying directly fossil and non-fossil contributions to carbonaceous aerosol, by means of radiocarbon measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In particular, the enrichment in Ca 2+ could be attributed to dust from soil resuspension in urban and suburban environments (no transport of desert dust was observed during this field campaign), while K + enrichment could testify to the significant use of biomass burning for heating systems; this observation was particularly true at the NAP site, due to the accumulation of K + in the smaller particles (PM 2.5 fraction). The higher contribution from anthropogenic sources was also supported by the measured organic/elemental carbon (OC/EC) content at the same site [19,65]. In that work, the authors analyzed the carbon content in PM from the same monitoring campaign and showed that the highest levels were achieved in Naples (12.8 ± 5.1 and 11.8 ± 4.6 µg/m 3 for organic carbon in PM 10 and PM 2.5 ; 2.3 ± 1.1 and 1.8 ± 0.5 µg/m 3 for elemental carbon in PM 10 and PM 2.5 ).…”
Section: Sea Salt Contributionmentioning
confidence: 68%
See 1 more Smart Citation
“…In particular, the enrichment in Ca 2+ could be attributed to dust from soil resuspension in urban and suburban environments (no transport of desert dust was observed during this field campaign), while K + enrichment could testify to the significant use of biomass burning for heating systems; this observation was particularly true at the NAP site, due to the accumulation of K + in the smaller particles (PM 2.5 fraction). The higher contribution from anthropogenic sources was also supported by the measured organic/elemental carbon (OC/EC) content at the same site [19,65]. In that work, the authors analyzed the carbon content in PM from the same monitoring campaign and showed that the highest levels were achieved in Naples (12.8 ± 5.1 and 11.8 ± 4.6 µg/m 3 for organic carbon in PM 10 and PM 2.5 ; 2.3 ± 1.1 and 1.8 ± 0.5 µg/m 3 for elemental carbon in PM 10 and PM 2.5 ).…”
Section: Sea Salt Contributionmentioning
confidence: 68%
“…It is within a restricted traffic area and near to the marina, but not far from heavily trafficked roads. It is influenced by multiple sources, e.g., vehicular traffic, port emissions and biomass combustion from the numerous pizza restaurants nearby, combined with widespread pollution conditions [17][18][19][20][21][22]. Lecce (LEC, 40.3°N, 18.1°E) is an urban background site located on the roof of CNR-ISAC (Istituto di Scienze dell'Atmosfera e del Clima, Italian National Research Council) at 12 m above ground level and about 4 km south-west of Lecce town center.…”
Section: Site Descriptionmentioning
confidence: 99%
“…In addition, the harbours are close to a densely populated urban area (about 1,000,000 inhabitants), which is characterized by the presence of many other pollutant emission sources: vehicular traffic, domestic and commercial combustions and air traffic due to the nearby Capodichino Airport. These sources determine the air quality in the urban area, which is characterized by severe PM pollution (Agrillo et al 2013;Chianese et al 2019;Dinoi et al 2017;Riccio et al 2014;Sirignano et al 2019).…”
Section: Site Description and Sampling Methodsmentioning
confidence: 99%
“…Currently available data about EC and OC for the urban area of Naples were reported in studies conducted by Dinoi et al (2017) and by Sirignano et al (2019). In these studies, it was hypothesized that the sampling site, located in the centre of the urban area of Naples (close to marina, at 53 m a.s.l.…”
Section: Oc/ecmentioning
confidence: 99%
“…In contrast, biomass combustion is highly variable, depending on the biomass resource and the burning conditions. The ratio can vary from ~1 to >5, e.g., [51,52]. A ratio of <~1.9 could be interpreted as the primary aerosol associated with motor vehicle and biomass burning emissions alone.…”
Section: Particle Compositionmentioning
confidence: 99%